Wearable and IoT technologies application for physical rehabilitation - Alexandre, R.; Postolache, O. (2018 International Symposium in Sensing and Instrumentation in IoT Era, ISSI 2018, 2018)
This paper presents a set of smart gloves to be used for natural interactions with therapeutic serious games for upper limb rehabilitation. These games provide to the patients with motor impairments the possibility to perform exercises in a highly interactive way based on different VR scenarios. The system is composed by a set of software tools that support the collection and processing of data as so as a set of highly interactive therapeutic games to include in hand and finger rehabilitation session exercises. The acquired data help the physiotherapist to evaluate the patients' performance throughout the different physical activities during a rehabilitation session. The data acquisition is fulfilled by an Arduino Nano computation platform connected to the analog measurement channels materialized by piezo-resistive force sensors. The data communication between the smart sensors and the VR computation platform is performed using Bluetooth wireless communication protocol. Some metrics associated with the upper limb training were also developed to evaluate the patient motion during the training session. Several tests and experimental results are included in the paper.